Introduction To Probability
Introduction to Probability features exceptionally clear explanations of the mathematics of probability theory and explores its diverse applications through numerous interesting and motivational examples. It provides a thorough introduction to the subject for professionals and advanced students taking their first course in probability. The content is based on the introductory chapters of Roussas\\\'s book, An Intoduction to Probability and Statistical Inference , with additional chapters and revisions.Readership This one-semester basic probability textbook is written for students in mathematics, physics, engineering, statistics, actuarial science, operations research, and computer science